Optimalisasi Edukasi Kebersihan Lingkungan Berbasis Phbs Melalui Pengembangan SDM Masyarakat Kelurahan Wijaya Kusuma, Grogol Petamburan - Yonia Farera; Miftahul Buchoiry; Sela Martin; Junias Robert Gultom (Lembaga Pengembangan Kinerja Dosen, 2026)
Environmental cleanliness in urban areas remains an important issue because it affects both public health and the quality of daily life. However, the implementation of Clean and Healthy Living Behavior (PHBS) continues to face various challenges, particularly due to limited public awareness and community involvement in maintaining environmental hygiene. This Community Service Program was conducted in Wijaya Kusuma Village, Grogol Petamburan District, with the aim of strengthening environmental cleanliness education through the development of community human resources based on PHBS principles. The program adopted a participatory approach consisting of field observations, educational sessions, interactive discussions, and community clean-up activities. Data were collected through direct observation, activity documentation, and participants' responses throughout the implementation of the program. The findings indicate that the community responded positively to the entire series of activities, as reflected by greater involvement in environmental clean-up efforts and increased attention to the application of PHBS in daily life. Furthermore, active community participation fostered stronger collaboration among residents and encouraged a shared commitment to maintaining a clean, healthy, and sustainable environment. Therefore, participatory PHBS-based education can serve as an effective strategy for promoting environmental health and encouraging sustainable healthy living practices within the community.